Education And Detection Of Diabetes Mellitus In Pre-Menopausal And Menopausal Women In The Subdistrict Of Pekan Arba Tembilahan - Meyrent, Wita; Pramana , Cipta; Dewi , Novita Puspita (Jurnal Pengabdian Mandiri, 2025)
The lack of knowledge among premenopausal and menopausal women about the possibility of developing diabetes mellitus can lead to delayed detection and management of the condition. Diabetes mellitus in premenopausal and menopausal women is a condition that occurs when the body is unable to regulate blood sugar levels properly. This can cause a variety of serious health problems. Premenopausal and menopausal women have a higher risk of developing diabetes than men. This is due to hormonal changes, decreased muscle mass, and increased body fat that occur during this period. Understanding Diabetes Mellitus is very important for premenopausal and menopausal women because with a good understanding, women can improve their quality of life. Many problems will arise if women do not have good knowledge about health disorders in their old age. Therefore, by providing education about Diabetes Mellitus, it is hoped that the knowledge of premenopausal-menopausal women can be improved and their behaviour influenced so that they become more concerned about their health. The methods used were lectures and group discussions that took place interactively. A total of 10 premenopausal-menopausal women attended.